2016
DOI: 10.1016/j.bbi.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids enhance the in vivo migratory response of human monocytes

Abstract: Glucocorticoids (GCs) are best known for their potent anti-inflammatory effects. However, an emerging model for glucocorticoid (GC) regulation of in vivo inflammation also includes a delayed, preparatory effect that manifests as enhanced inflammation following exposure to an inflammatory stimulus. When GCs are transiently elevated in vivo following exposure to a stressful event, this model proposes that a subsequent period of increased inflammatory responsiveness is adaptive because it enhances resistance to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 62 publications
(83 reference statements)
2
28
0
Order By: Relevance
“…To explain the observed differences between transported and control animals and low and normal body weight calves, the most likely mechanism is the effect of serum cortisol concentration. Depending on the concentration, cortisol can have suppressive, stimulatory, and also preparatory effects on the immune system. Preparatory effects can be observed when a transient (hours) in vivo exposure to stress‐induced GC concentrations is followed by a return to normal, basal concentrations and are caused by transcriptional and phenotypic changes in immune effector cells that prime them for enhanced responses to a subsequent immune stimulus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explain the observed differences between transported and control animals and low and normal body weight calves, the most likely mechanism is the effect of serum cortisol concentration. Depending on the concentration, cortisol can have suppressive, stimulatory, and also preparatory effects on the immune system. Preparatory effects can be observed when a transient (hours) in vivo exposure to stress‐induced GC concentrations is followed by a return to normal, basal concentrations and are caused by transcriptional and phenotypic changes in immune effector cells that prime them for enhanced responses to a subsequent immune stimulus .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the concentration, cortisol can have suppressive, stimulatory, and also preparatory effects on the immune system. Preparatory effects can be observed when a transient (hours) in vivo exposure to stress‐induced GC concentrations is followed by a return to normal, basal concentrations and are caused by transcriptional and phenotypic changes in immune effector cells that prime them for enhanced responses to a subsequent immune stimulus . These effects typically manifest several hours after transient exposure to stress‐increased GCs and might last for up to a week .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has not been investigated in the context of CWI, but Yeager et al . () found that monocytes and neutrophils did indeed migrate into sterile blister fluid in response to a dose of cortisol corresponding to that released during acute stress. The 29% increase in resting monocyte levels over 6 weeks of CWI reported by Janský et al .…”
Section: Introduction: Historymentioning
confidence: 98%
“…49,50 This suggests that a Dex-dependent decrease in serum MCP-1 may be compensated for by an increase in CCR2. Consistent with this, flow cytometric analysis of circulating monocytes revealed that Dex-naïve GBM patients have fewer CCR2+ cells, but Dex treatment restored CCR2 frequencies to those seen in healthy donors (Figure 4G).…”
Section: Resultsmentioning
confidence: 99%